CORRELATION ANALYSIS OF TWO KIND OF SWIMMING STARTS AND THE FINAL TIME IN THE 50 METERS FREESTYLE IN MEN AND WOMEN (Fiep Bulletin - online, 2014)
In the competitive swimming we observe two kinds of starts: grab start (GS) and track start (TS). The starts vary as the preference and the training that the swimmer carries through or determination techniques. Issurin and Verbitsky (2002) affirming that the techniques of start in swimming can present when comparative particular advantages between itself. Maglischo (1999) and Coulsiman (1984) confirm that the execution of a good start is basic to a good result. The start techniques in championships can be used in the training with the objective the perfection (VILLAS-BOAS E FERNANDES, 2003). The main of this study was to verify two types of starts used for the swimmers in the 50 meters freestyle in both genders, and to correlate with the performance during the Brazilian Swimming Championship 2005. The sample was of 36 women and 33 men. The tape film analyses was made in a second time and was compared with the final time of each swimmer, verified through the Correlation of Sperman. No had been found significant statistical differences in the starts in both genders in the Brazilian Championship, through the final time analysis; also correlation was not found between the employed start kind and the final time. Therefore, we concludes that it does not have significant correlation and significant difference between start chosen and the final time reached in the 50 meters freestyle in both genders.
Keywords: Start of grab start; track start; correlation